Mineral Components In Different Varieties Of Sweet Potato (Texas Journal of Philology, Culture and History, 2024)
This article contains information on the amount of macro and micronutrients in the leaves of sweet potato varieties. Khazina, Khazina 2, Khazina 3, Khazina 4 and GulDU varieties of sweet potatoes were selected as the object of research. The amount of nitrate form of nitrogen in sweet potato leaves is 4.03, phosphorus - 53.2 per 100 g. potassium -44.1 mg, iron -19.8, molybdenum -56.3, sulfate -93.1, boron -0.9, zinc -0.43, chlorine (mg/l) - 19.9 and copper 1.80 mg. It was noted that the majority of microelements was sulfate ion. It was found that the new varieties Khazina-2 and Khazina 4 of Batat differed in the amount of macro and micronutrients compared to other varieties.